2013 AGU Medalists, Awardees, and Prize Recipient Announced. (30th July 2013) - Finn, Carol; McKenzie, Judith Ann
Abstract : The Honors and Recognition Committee is proud to present the 2013 AGU honorees. These individuals have distinguished themselves by their transformational discoveries, persistence, dedication, and pursuit of excellence. We are pleased to recognize their breakthrough achievements in advancing Earth and space science and their outstanding contributions and service to the scientific community. Their passion, vision, creativity, and leadership have expanded our scientific understanding, have illuminated new research directions, and have made Earth and space science thrilling, immediate, and relevant to audiences beyond as well as within the scientific community.